Testing marine regional-scale hypotheses along the Yucatan continental shelf using soft-bottom macrofauna - Hernandez-Avila, Ivan; Ocaña, Frank A.; Pech, Daniel (PeerJ, 2020)
Different hypotheses related to the regional-scale configuration of the Yucatan Continental Shelf (YCS) between the Gulf of Mexico (GoM) and the Caribbean Sea have been proposed. Hypotheses regarding its regional boundaries include: (i) an ecoregional boundary at Catoche Cape, dividing the Western Caribbean and the Southern GoM ecoregions; and (ii) a boundary within the Southern GoM ecoregion at 89°W, separating the West and Mid-Yucatan areas. We tested the hypothesis of no variation in benthic macrofaunal assemblages between regions delimited by the former boundaries using the species and functional traits of soft-bottom macrofauna. We considered that the depth and temporal environmental dynamics might interact with regional variations, generating complex benthic community patterns. The data were collected over five years (2010–2012, 2015–2016) at 86 stations (N = 1, 017 samples, 10–270 m depth), comprising 1,327 species with 45 combinations of functional traits. The variation in species composition and functional trait assemblages were both consistent with the occurrence of three separate regions in the Yucatan Peninsula (West Yucatan, Mid-Yucatan and Western Caribbean). This regional configuration was consistent with changes in assemblage structure and depth zonation as well as temporal variation. Along with spatial and temporal variation, diversity diminished with depth and different regions exhibited contrasting patterns in this regard. Our results suggest that the spatial and temporal variation of soft-bottom macrofauna at YCS demonstrate the complex organization of a carbonate shelf encompassing different regions, which may represent transitional regions between the Caribbean and the GoM.
Keywords: Biodiversity; Gulf of Mexico; Continental Shelf; Macrofauna; Functional traits; Species assemblage; Calcareous sediments; Western Caribbean